Catatonia, Pregnancy, and Electroconvulsive Therapy (ECT) - Gandhi, Khushbu; Nguyen, KieuHanh; Driscoll, Maggie; Islam, Zahid; Maru, Siddhartha (Case Reports in Psychiatry, 2023)
Background. Catatonia is a neuropsychiatric syndrome, which typically occurs in the context of another psychiatric or medical condition, with a significant morbidity and mortality risk. Significant medical conditions resulting from catatonia include nutritional deficiencies, skin ulcerations, electrolyte disturbances, aspiration pneumonia, and venous thromboembolism. As a result, prompt treatment is required. Gold standard treatment consists of benzodiazepines, followed by electroconvulsive therapy (ECT) if pharmacotherapy alone is ineffective. With pregnancy and catatonia, there is a high risk of adverse maternal/fetal outcomes, and the risks/benefits of treatment must be carefully considered. Case. Here, we present a case of a young pregnant woman with schizoaffective disorder whose catatonic state was not successfully resolved with lorazepam, therefore requiring ECT. Patient presented to the emergency department at 20 weeks of pregnancy, displaying symptoms of catatonia and psychosis. She was admitted to the inpatient behavioral health unit, where she was treated with lorazepam for catatonia. Treatment occurred in close collaboration with the obstetrics team. While initially, the patient appeared to have a positive response to lorazepam, she became increasingly catatonic with minimal oral intake, mutism, and urinary retention. As a result, she was transferred to the medical floor, where ECT was initiated due to the ineffectiveness of lorazepam. Her catatonia was successfully resolved with 12 total treatments of ECT; there were no adverse effects to the fetus. Patient delivered her baby at 39 weeks with no complications. She continued to receive inpatient psychiatric care until she was stable for discharge to an extended acute care unit. Objectives. In this report, we will review relevant literature on catatonia in pregnancy, with focus on treatment with ECT. Conclusions. Though the literature on these topics is limited and typically presented in case reports format, there appears to be a favorable view toward the use of ECT for pregnant catatonic patients. This case could be considered a vital contribution to the literature, as it provides a successful example of treating catatonia in pregnancy with no known adverse effects to the mother or child.